2022
DOI: 10.18502/ijm.v14i2.9184
|View full text |Cite
|
Sign up to set email alerts
|

Rapid identification of carbapenemases by CarbAcineto NP test and the rate of beta-lactamases among Acinetobacter baumannii from a teaching hospital

Abstract: Background and Objectives: Acinetobacter baumannii has emerged as a major organism accounting for hospital acquired infections particularly in intensive care units. Due to production of different kinds of beta lactamases these bacteria have developed drug resistance rendering the treatment of such infections very difficult and expensive. Rapid identification of A. baumannii producing such beta-lactamases is the need of the hour in reducing morbidity and mortality associated with A. baumannii infections. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
1
0
0
Order By: Relevance
“…In order to fight against the emergence and spread of multiresistant bacteria, this study aimed to determine the prevalence and risk factors of carbapene- In the present study, 88 (52.69%) clinical isolates included were from male patients with highest number of isolates from patients aged between 10 -39 years old. This is in line with a recent study realized by Rao et al which reported a high proportion of males (81.8%) [17]. These findings suggest that male and elderly were more vulnerable for infections in both studies.…”
Section: Discussionsupporting
confidence: 93%
“…In order to fight against the emergence and spread of multiresistant bacteria, this study aimed to determine the prevalence and risk factors of carbapene- In the present study, 88 (52.69%) clinical isolates included were from male patients with highest number of isolates from patients aged between 10 -39 years old. This is in line with a recent study realized by Rao et al which reported a high proportion of males (81.8%) [17]. These findings suggest that male and elderly were more vulnerable for infections in both studies.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study 88 (52.69%) clinical isolates included were from male patients with highest number of isolates from patients aged between 10-39 years old. In accordance to the current study, Rao et al also observed male predominance (81.8%) [15]. These findings suggest that male elderly were more vulnerable for infections in both the studies.…”
Section: Discussionsupporting
confidence: 92%